2012
DOI: 10.1007/s12263-012-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors modify obesity risk linked to PPARG2 and FTO variants in an elderly population: a cross-sectional analysis in the SUN Project

Abstract: Genetic factors may interact with lifestyle factors to modify obesity risk. FTO and PPARG2 are relevant obesogenes. Our aim was to explore the effect of Pro12Ala (rs1801282) of PPARG2 and rs9939609 of FTO on obesity risk and to examine their interaction with lifestyle factors in an elderly population. Subjects (n = 978; aged 69 ± 6) were recruited from the SUN (Seguimiento Universidad de Navarra) Project. DNA was obtained from saliva, and lifestyle and dietary data were collected by validated self-reported que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…A report on elderly university alumni from Spain, the SUN study, found that FTO associations with obesity-risk might depend on high carbohydrate intake [22]. If we take into account the BMI of study participants when they are young for genetic association analyses, we could begin to understand the accumulative effect of lifestyle events.…”
Section: Discussionmentioning
confidence: 99%
“…A report on elderly university alumni from Spain, the SUN study, found that FTO associations with obesity-risk might depend on high carbohydrate intake [22]. If we take into account the BMI of study participants when they are young for genetic association analyses, we could begin to understand the accumulative effect of lifestyle events.…”
Section: Discussionmentioning
confidence: 99%
“…The risk allele 12Ala has been linked to increased obesity risk through meta-analysis, although some heterogeneous effects of this mutation have also been observed in interaction studies [148][149][150]. Lamri et al [151] analysed the interaction between PPARG Pro12Ala polymorphism and fat intake, and observed that AlaAla individuals displayed greater BMI values than Pro carriers among high fat consumers.…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 99%
“…It is widely recognised that there is an inverse relationship between obesity and physical activity practice ( Levine 2005;Galbete et al, 2012;Kilpelainen et al, 2011). In fact, some studies have revealed association between genetic variants and physical activity (Galbete et al, 2012;Kilpelainen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some studies have revealed association between genetic variants and physical activity (Galbete et al, 2012;Kilpelainen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%